Features of economic results management of agricultural enterprises - Vinichenko, Ihor; Вініченко, Ігор Іванович; Sitkovska, Alla; Сітковська, Алла Олександрівна; Horniuk, Denys; Горнюк, Денис Ігорович (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
The article considers the economic results of agrarian enterprises as an economic category that reflects the effectiveness of the agrarian enterprise. The existing significant features of formation of economic results in agricultural enterprises, which are due to the production and economic specifics of the industry, namely: the influence of natural and climatic factors (seasonality of production); multiindustry nature of activities; impact on economic outcomes of biological factors; processing of own and ancillary raw materials; calculation of production cost. The tasks that are necessary for managing the economic results of the agricultural enterprise are highlighted. The main tendencies of development of competitive environment of functioning of agrarian enterprises are highlighted. It was established that, provided the formation of an entrepreneurial environment as an association of enterprises, agrarian enterprises get better competitive positions, and accordingly higher economic results. Given that some types of entrepreneurships are formed by attractinglargescale investments and a high-tech production base, others are based on individual activities using lowtechproduction facilities, and the professional abilities of the management cause differences in the way of organization and management of the enterprise, so the affiliation of the enterprise to small or large is determined by the effectiveness of its economic activities. The size of agricultural enterprises necessary for the appropriate type of activity will be recognize s effective. The significant impact on the size and formation of economic results of agricultural enterprises is indicated: their distribution according to the size criterion. Large enterprises have a competitive potential and a sufficient level of competitiveness in the field of large business, but they are not competitive enough in small production, on the contrary, the competitive advantages of small enterprises appear only in small business. In case of high-grade production type, as opposed to small-scale production, there is a decrease in the cost of the unit of sold products with an increase in the volume of its sales, that is, the economies of scale are achieved. If this process does not occur, then there is a phenomenon of negative economies of scale. Internal losses on the scale can arise because of the fact that by increasing the optimal volumes of agricultural sales, high welded agricultural enterprises are forced to disproportionately increase and retaina large number of administrative workers. External economies of scale arise from the increased application of innovation by enterprises. An enterprise with an optimal level of production concentration (under equal other conditions) can function more economically. The priority tasks are outlined, which are presented to agricultural enterprises and contribute to increasing the effectiveness of their activities. The role of qualified personnel is considered, which acts as the main factor in the system of management of economic results of an agrarian enterprise. Зазначено суттєвий вплив на формування економічних результатів аграрних підприємств розподіл їх за критерієм розміру, розкриті їх переваги та недоліки. Визначено, що великі підприємства володіють конкурентним потенціалом і достатнім рівнем конкурентоспроможності в сфері великого бізнесу, але вони недостатньо конкурентоспроможні в дрібному виробництві, навпаки, конкурентні переваги малих підприємств проявляються лише в дрібному бізнесі. Окреслені пріоритетні завдання, які постають перед аграрними підприємствами та сприяють підвищеннюрезультативності їх діяльності. Розглянута роль кваліфікованого персоналу, що виступає основним фактором у системі управління економічними результатами аграрного підприємства. Зроблено висновок, що управління економічним результатом є надзвичайно важливим аспектом діяльності підприємства, що досягається за рахунок проведення ряду організаційно економічних заходів.
Особливості управління економічними результатами діяльності аграрних підприємств
Keywords: management; управління; economic results; економічні результати; profit; прибуток; loss; збиток; agrarian enterprise; аграрне підприємство